Biofilm production by Staphylococcus Sp on stainless steel chips in contact with Brazilian Minas cheese homogenates and BHI broth under different extrinsic factors - Silva, Nathália C.C.; Bonsaglia, Érika C.R. [UNESP]; Júnior, Ary Fernandes [UNESP]; Hernandes, Rodrigo T. [UNESP]; Pantoja, José C.F. [UNESP]; Rall, Vera L.M. [UNESP] (Slovak University of Agriculture in Nitra, 2017)
The aim of this study was to evaluate biofilm production by Staphylococcus sp on stainless steel using brain heart infusion (BHI) broth and Minas Frescal cheese broth, at different levels of contamination and under different temperatures, atmospheres. The cheeses were classified according to their microbiota. It was evaluated biofilm formation on stainless steel chips at 8, 15 and 35°C after 48, 72 and 96 h under different conditions. Both Staphylococcus isolates formed biofilm on stainless steel chip in BHI broth and cheese broth, under all temperatures and atmospheres studied. In conclusion, BHI broth and Brazilian Minas cheese homogenate performed equally well for biofilm formation tests using Staphylococcus strains, and S. aureus can produce biofilm on stainless steel at 8°C, which may be a concern for the dairy industry. Finally, it is important to consider that S. aureus can be a good competitor, depending on the nature of the microbiota.
Keywords: Atmosphere; Biofilm; Microbiota; Staphylococcus aureus; Temperature